Ophiosimulans tanaceti gen. et sp. nov. (Phaeosphaeriaceae) on Tanacetum sp. (Asteraceae) from Italy - Saowaluck Tibpromma (2018)
© 2016, German Mycological Society and Springer-Verlag Berlin Heidelberg. Collections of microfungi on Tanacetum sp. (Asteraceae) in Italy resulted in the discovery of a new genus with characteristics similar to Ophiobolus. Phylogenetic analysis of sequence data showed that the new collection is a sister group to Ophiobolus and a new genus with morphologically distinct characters. In this paper, we introduce Ophiosimulans in the family Phaeosphaeriaceae with O. tanaceti as the type species. A detailed description and illustrations are provided and the new taxon is compared with similar genera in Phaeosphaeriaceae. Ophiosimulans is characterized by cylindrical asci with short pedicels and filiform ascospores with up to 15 septa, separating into two parts in the centre of the spore. Since Leptosphaeria tanaceti is also known from Tanacetum, we examined the syntype to compare it with Ophiosimulans, and provide an illustrated account of the species.